Sustainable Rebuilding: From Local Methodologies to Global Strategies - Nielsen, Adam Linde; Jaimini, Bhawna (MAJ - Malaysia Architectural Journal, 2025)
This paper will trace various traditions of rebuilding practices within architecture. From vernacular rebuilding methods to contemporary repairing architecture culture, the paper will be probing the context, conditions, and culture within these practices. As the world is becoming an increasingly vulnerable and volatile place, with looming threats of war, climate crisis and general unrest, the need for sustainable rebuilding is apparent all over the world. In this paper we will investigate how local rebuilding challenges can benefit from international collaboration and knowledge exchange. Some answers on how to repair and rebuild sustainably might be found in the vernacular building traditions. These traditions are not only ecologically sensitive but are also rooted in the idea of local community building and are deeply connected to our common planetary boundaries. However, through the technological advancements of the 20th century, and the need to build fast for a growing population, the vernacular building cultures are becoming increasingly replaced by a global modernist architecture. An often context-stripped architecture, which is proving neither good for the planet, nor for the people. This paper will analyze and explore the methods used within sustainable rebuilding and will discuss how they can contribute to a more locally anchored vernacular framework, where building cultures and knowledge is exchanged internationally. It will investigate how local methodologies have the potential to generate global strategies through international collaborations. It will do so through a carefully selected number of case studies representing different rebuilding challenges throughout the international community. The research presented in this paper will strive to be a contribution to the understanding of sustainable rebuilding and international collaboration. It will exemplify how local rebuilding methodologies, through care, compassion, and collaborations, can become global crises tackling strategies.